(untitled) (Pedagogy of Higher and Secondary Education, 2022)
The article with intonation ear elaboration problems of elementary school pupils. It analyses the vocal zone character and factors, which have an influence on the intoning clarity, and examines some methodological principles of intonation ear elaboration of pupils the tune basis.